India Economic Update, December 2010 - World Bank (Washington, DC, 2017)
The Indian economy recovered from the slowdown at the time of the global financial crisis with strong Gross Domestic Product (GDP) growth, in particular over the first half of FY2010-11. The agricultural sector bounced back strongly after the 2010 monsoon brought normal levels of rainfall, and the industrial sector registered double-digit growth for three consecutive quarters. Inflation came down to 7.5 percent in November but then accelerated again to 8.4 percent in December because of a renewed food supply shock. The current account deficit in FY2009-10 was the largest ever (in US$ terms) and the monthly deficit widened further during the first half of FY2010-11, but the trend then reversed with import growth slowing and export growth accelerating in September-December 2010. With the significant inflation differential between India and its trading partners, the rupees real effective exchange rate (REER) strengthened. On the fiscal side, massive windfall revenue from wireless spectrum auctions and buoyant tax revenue are likely to be offset by two supplementary spending bills. Monetary policy tightening continued with increases in policy rates. This update also discusses several medium-term issues: the link between the real exchange rate and growth, a long-term look at education, demographics and growth, the challenges facing the introduction of the Goods and Services Tax (GST), and the mid-term evaluation of the eleventh development plan. On the real exchange rate, economists have pointed out that the most successful emerging market economies have maintained an undervalued exchange rate to promote exports. In India, the real exchange rate has been broadly stable since the early 1990s, and the International Monetary Fund (IMF) judges it fairly valued with respect to different measures of equilibrium. However, the growing trade deficit and a large fiscal deficit do not quite fit this picture. Discussing policies, we argue that it would be best to focus on policies that increase productivity and competitiveness.